Pneumatic Displacement with Perfluoropropane Gas and Intravitreal Tissue Plasminogen Activator for Subretinal Subfoveal Hemorrhage after Focal Laser Photocoagulation in Central Serous Chorioretinopathy - Khalid Al Rubaie; Juan V. Espinoza; Andres F. Lasave; Dario Savino-Zari; Fernando A. Arevalo; J. Fernando Arevalo (Case Reports in Ophthalmological Medicine)
Objective. To report the visual and anatomic outcomes of pneumatic displacement with perfluoropropane (C3F8) gas and intravitreal tissue plasminogen activator (IVTPA) for subretinal subfoveal hemorrhage after focal laser photocoagulation in central serous chorioretinopathy (CSCR). Method. Interventional, retrospective case report of one eye (one patient). Outcome measures included visual acuity (VA), central macular thickness (CMT), and size of the lesion at two weeks of followup. Fluorescein angiography (FA) and optical coherent tomography (OCT) were used to measure anatomic outcomes. Results. A 35-year-old man with history of chronic CSCR received focal laser photocoagulation in the right eye two days before presentation. At initial examination, VA was 20/200 (ETDRS chart), CMT was 398 μ, and a subretinal subfoveal hemorrhage was seen. Tissue plasminogen activator (tPA) at a dose of 25 µg/0.1 mL was injected intravitreally before intravitreal C3F8 injection, and prone positioning was indicated postoperatively. At 24 hours, the hemorrhage had been displaced inferiorly and VA improved to 20/100. Two weeks later, VA improved to 20/80, CMT decreased to 225 μ, and the hemorrhage decreased without foveal involvement. Conclusions. The technique seems safe and effective in treating visually significant subretinal subfoveal hemorrhage.